Potret Pernikahan Dini di Indonesia (Studi Kasus di Desa Jatimulyo Kabupaten Lumajang) - Nurie Azizah; Fauzik Lendriyono; Oman Sukmana (Universitas Muhammadiyah Sumatera Utara, 2021)
This research examines the reasons for early marriage in Jatimulyo Village and the impact that occurs in the family life. The research uses descriptive qualitative research in which the research data is based on data found in the field. The data collection method uses direct observation in Jatimulyo Village. Direct and-depth interviews, and documentation. The research subjects used case studies. The data analysis technique used was data reduction, data presentation, verification and coclusion drawing. The result showed: Marriage carried out at an early age does not always end ini divorce and also does not always end without problems, emotions and respect for partners are very important in a marriage relationship. As for the impact to early marriage that occurs in family life, namely for couples whose marriage smoothly have a beneficial impact on both parties, both parents and marriage couples. Appart for adding new family members, it alsi strengthens brotherhood. For couples whose marriages do not run smoothly, it has an impact on the loose ties of brotherhood and experiences a burden on the mindKeywords: early marriage, teenagers, Jatimulyo village.